Comparative Performance of Comorbidity Indices in Predicting Health Care-Related Behaviors and Outcomes among Medicaid Enrollees with Type 2 Diabetes - Ou, Huang-Tz (Popul Health Manag, 2012)
No single gold standard of comorbidity measure has been identified, and the performance of comorbidity indices vary according to the outcome of interest. The authors compared the Charlson Comorbidity Index, Elixhauser Index (EI), Chronic Disease Score (CDS), and Health-related Quality of Life Comorbidity Index (HRQL-CI) in predicting health care-related behaviors (physicians' concordance with diabetes care standards and patients' oral antidiabetic drug [OAD] adherence) and outcomes (health care utilization and expenditures) among Medicaid enrollees with type 2 diabetes. A total of 9832 diabetes patients who used OAD were identified using data from the MarketScan Medicaid database from 2003 to 2007. Predictive performance of the comorbidity index was assessed using multiple regression models controlling for patient demographics, diabetes severity, and baseline health care characteristics. Among the 4 indices, the CDS was best at predicting physician's concordance with care standards. The CDS and HRQL-CI mental index performed better than other indices as predictors of medication adherence. The EI was best at predicting health care utilization and expenditures. These results suggest that, for these low-income diabetes patients, the CDS and HRQL-CI mental index were relatively better risk-adjustment tools for health care-related behavior data evaluation and the EI was the first choice for health care utilization and expenditures data. (Population Health Management 2012;15:220–229)